Labor Dystocia: Uses of Related Nomenclature. (October 2015) - Neal, Jeremy L.; Ryan, Sharon L.; Lowe, Nancy K.; Schorn, Mavis N.; Buxton, Margaret; Holley, Sharon L.; Wilson‐Liverman, Angela M.
Abstract : Introduction: Labor dystocia (slow or difficult labor or birth) is the most commonly diagnosed aberration of labor and the most frequently documented indication for primary cesarean birth. Yet, dystocia remains a poorly specified diagnostic category, with determinations often varying widely among clinicians. The primary aims of this review are to 1) summarize definitions of active labor and dystocia, as put forth by leading professional obstetric and midwifery organizations in world regions wherein English is the majority language and 2) describe the use of dystocia and related terms in contemporary research studies. Methods: Major national midwifery and obstetric organizations from qualifying United Nations‐member sovereign nations and international organizations were searched to identify guidelines providing definitions of active labor and dystocia or related terms. Research studies (2000‐2013) were systematically identified via PubMed, MEDLINE, and CINAHL searches to describe the use of dystocia and related terms in contemporary scientific publications. Results: Only 6 organizational guidelines defined dystocia or related terms. Few research teams (n = 25 publications) defined dystocia ‐related terms with nonambiguous clinical parameters that can be applied prospectively. There is heterogeneity in the nomenclature used to describe dystocia, and when a similar term is shared between guidelines or research publications, the underlying definition of that term is sometimes inconsistent between documents. Discussion: Failure to define dystocia in evidence‐based, well‐described, clinically meaningful terms that are widely acceptable to and reproducible among clinicians and researchers is concerning at both national and global levels. This failure is particularly problematic in light of the major contribution of this diagnosis to primary cesarean birth rates.